The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/j.jesp.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Suspicion of motives predicts minorities' responses to positive feedback in interracial interactions

Abstract: Strong social and legal norms in the United States discourage the overt expression of bias against ethnic and racial minorities, increasing the attributional ambiguity of Whites’ positive behavior to ethnic minorities. Minorities who suspect that Whites’ positive overtures toward minorities are motivated more by their fear of appearing racist than by egalitarian attitudes may regard positive feedback they receive from Whites as disingenuous. This may lead them to react to such feedback with feelings of uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 87 publications
(110 reference statements)
7
67
1
Order By: Relevance
“…As previous research on attributional ambiguity theory has relied upon carefully scripted feedback and confederate responses (e.g., Crocker et al, 1991;Major, Kaiser, & McCoy, 2003;Major et al, 2016;Mendes et al, 2008), these situational manipulations precluded tests of social accuracy. The current results fill this gap in the attributional ambiguity literature by employing the SOMI.…”
Section: Discussionmentioning
confidence: 99%
“…As previous research on attributional ambiguity theory has relied upon carefully scripted feedback and confederate responses (e.g., Crocker et al, 1991;Major, Kaiser, & McCoy, 2003;Major et al, 2016;Mendes et al, 2008), these situational manipulations precluded tests of social accuracy. The current results fill this gap in the attributional ambiguity literature by employing the SOMI.…”
Section: Discussionmentioning
confidence: 99%
“…Research evaluating threat response and discrimination has suggested that individuals may experience a greater stress response when they are given feedback that is discrepant to their performance, especially when the feedback is provided by individuals of different racial/ethnic backgrounds (Major, Kunstman, Sawyer, Townsend, & Mendes, 2016). …”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…While racial color blind strategies may ostensibly be used to foster the same treatment of all, the ultimate goal in employing these tactics may be more related to self‐presentation concerns and masking bias rather than preventing it. Notably, recent research has demonstrated that attempts to appear nonprejudiced, such as avoiding negativity, may not be well‐received by racial minority group members (Major et al., ). In fact, Black participants who were suspicious of White interaction partners’ motives reacted negatively to positive evaluations and found the feedback of Whites to be disingenuous.…”
Section: Discussionmentioning
confidence: 99%